A nanoelectromechanical systems optical switch driven by optical gradient force - Dong, Bin (2013)
A nanoelectromechanical systems (NEMS) optical switch driven by optical gradient force is demonstrated. The switch consists of a free-standing ring resonator and two bus waveguides. When the free-standing ring is bended by the optical gradient force, the output transmission signal is tuned from the on-state to the off-state of the switch. The NEMS optical switch shows a switching time of 43.5 ns and a switching contrast of more than 25 dB. With its chip-scale integrability, the optical switch has potential applications in signal processing and high-speed optical communication networks.